STRATEGI PEMASARAN ONLINE SHOP: UPAYA UNTUK MENINGKATKAN VOLUME PENJUALAN - Kamilil Muhimmah; Moh. Rofiki (Jurnal Istiqro, 2021)
The emergence of a practical online shopping shift on social media has a major impact on people's perspectives and behavior. Many people don't want to have trouble shopping, so the Tunas Handmade store uses this opportunity to introduce their products to people who are engaged in crafts and skills. The products produced by the Tunas Handmade shop were created by the shop owner himself who departed from his hobby of hand skills. The research method uses descriptive-qualitative analysis research methods in the form of case studies. Data collection techniques in this research use observation, interviews and documentation. The marketing strategy of the handmade tunas shop was initially through direct marketing, in the form of sales made at home and the dissemination and delivery of information by word of mouth which was considered less effective. Toko Tunas Handmade uses Online Shop marketing via WhatsApp, Instagram and Facebook as a promotional tool to make it easier to convey business product information to the public. Online shop marketing is proven to be able to increase the sales volume of the Tunas Handmade store, seen from the addition of a 55% sales percentage.